Insights into a Renowned Fishery: Distinct Spatial Patterns, Environmental Predictors and Species Associations of Trophy-Class Spotted Seatrout (Cynoscion nebulosus [Cuvier 1830]) - Catherine Eckert; Elliot Briell; Ethan Getz (Fishes)
Spotted Seatrout Cynoscion nebulosus (hereafter, trout) are one of the most heavily targeted sportfish along the Gulf coast. With recent regulation changes intended to reduce the harvest mortality of trout and promote a healthy trophy-class trout fishery in Texas, understanding differences between trophy-class (>28 in, 712 mm) and adult-class (12–28 in, 305–710) trout has become especially relevant for fisheries managers. Here, we leveraged a long-term (1983–2023) gill net dataset collected by the Texas Parks and Wildlife Department to (1) compare the distribution of size classes both spatially and temporally, (2) determine environmental drivers of the abundance of each size class, and (3) compare the species associated with each size class in the Upper Laguna Madre. Kernel density distribution estimates, hot spot analyses, and space–time pattern mining methods were used to compare the distribution of the two size classes of trout spatially and temporally. Boosted regression trees (BRTs) were used to determine the environmental drivers of abundance, and multivariate analyses were utilized to compare the species associated with each size class. Trophy-class trout exhibited a greater degree of spatial clustering than adult-class trout, with abundance peaks concentrated along specific shorelines in Baffin Bay. Significant changes in trophy-class trout distribution over time were also found, indicating that the spatial clustering of trophy-class trout has intensified over the past four decades. Salinity and bay were strong predictors for the abundance of both size classes, with peak abundances of both trophy-class and adult-class trout in Baffin Bay and its tertiary bays and at salinities of 10–30 and above 60 psu. Dissolved oxygen (DO) concentration and temperature were good predictors of the abundance of trophy-class trout, which were most abundant at temperatures of 25–30 °C and DO levels of 5–8 mg/L. Depth, turbidity, and season were good predictors of the abundance of adult-class trout, which were most abundant at increased depths (>2 m), low-to-moderate turbidity (~125 NTU), and in the spring season (April–June). Multivariate analyses revealed differences in the communities associated with trophy-class and adult-class trout occurrence, with species such as Black Drum Pogonias cromis, Striped Mullet Mugil cephalus, and Ladyfish Elops saurus more abundant in samples associated with trophy-class trout. These results indicate that trophy-class trout display unique spatial patterns and species associations and that their abundance may be driven by a distinct set of hydrological and biotic factors, which may have important implications for the management of trophy fisheries.